Modern pollen analysis in caves at the Patagonian steppe, Argentina - de Porras, Maria Eugenia (2011)
Cave fossil records from the Patagonian steppe (Argentina) have been largely used as a source of archaeological and palaeoenvironmental information. Major uncertainties exist, however, regarding the degree to which the fossil pollen assemblages from caves reflect past environments because of the complex site formation processes and post-depositional bias. Studies within caves from other regions have demonstrated that the understanding of modern pollen taphonomy helps to recognise the record bias improving thus the inferences. The present study therefore aims to understand how modern plant communities are represented within two caves at the Patagonian steppe and to establish the modern pollen taphonomic processes. Cave pollen assemblages provided a good representation of the local vegetation indicating therefore that cave fossil pollen assemblages are a reliable source for inferring the past vegetation. However, the modern taphonomic analysis pointed out that cave pollen assemblages are not homogeneous but show spatial variability due to different factors. Vegetation distribution, physiognomy and pollination type, biotic transport and human disturbance were the major factors affecting the cave pollen assemblages whereas orientation and topographic position seemed not to be significant. Biotic transport caused unexpected deposition patterns while animal and human post-depositional disturbance the homogenization of pollen assemblages. Other factors such as the cave internal topography, morphology and microclimatic circulation might be determinant on floor pollen assemblages so should be further investigated.